Hydrodynamic Impedance of Bacteria and Bacteria‐Inspired Micro‐Swimmers: A New Strategy to Predict Power Consumption of Swimming Micro‐Robots for Real‐Time Applications. Issue 4 (5th March 2018) - Tabak, Ahmet Fatih
Abstract: Power supply is one of the key issues with bio‐inspired micro‐robots for therapeutic applications. There have been different approaches to predict the hydrodynamic behavior of such systems, most of which are based on the low‐Reynolds‐number approximation of the surrounding flow field, also known as the Stokes flow. However, it has been long debated that the Stokes‐flow approach without corrections for hydrodynamic interactions is inadequate in explaining the dynamics of a particle, even a blunt sphere, following a non‐trivial path subject to spatial and temporal variations. A cargo being towed by a rotating helical tail presents an even more complicated problem which can only be appreciated by numerical solutions of time‐dependent Navier–Stokes equations incorporated with rigid‐body dynamics. In this study, such a solution scheme is presented for the six degrees of freedom motion of both bacteria and bacteria‐inspired micro‐robots, swimming in backward or forward direction. Furthermore, the analysis is extended to characterize the impedance coefficients via parameterized wave geometry. Thus, it is demonstrated that the resistive force theory can be improved to predict time‐dependent fluid resistance acting on bio‐inspired micro‐swimmers via hydrodynamic impedance‐based corrections, allowing accurate calculation of required power to achieve desired actuation strategies. Abstract : Higher‐order effects are responsible for the out‐of‐phase behavior of rigid‐body velocity of bacteria‐like micro‐swimmers and associated fluid forces. Fast and linear hydrodynamic models that can be used for real‐time motion control applications are not accurate enough. In this study, a series of CFD analyses are employed to implement a strategy to obtain the corrections for the resistive force theory models.